Food Safety on the Farm – An Overview of Good Agricultural Practices - Renée M. Goodrich-Schneider; Keith R. Schneider; Douglas L. Archer (EDIS, 2006)
(also in FYCS Descriptions) FSHN06-01, a 3-page factsheet by Renee Goodrich Schneider, Keith R. Schneider, and Douglas L. Archer, provides background on and a description of these best practices for commercial producers and packers of fresh fruits and vegetables. This document gives a basic overview of the eight topics (water, manure and biosolids, worker health and hygiene, sanitary facilities, field sanitation, packing facilities, transportation, and traceback) that will be covered in detail in this series. Published by the UF Department of Food Science and Human Nutrition, November 2006.